A small scale wastewater treatment system adapted to nutrient recovery in cold climate : performance and possible sorbents - Amofah, Lea Rastas (Luleå tekniska universitet, Arkitektur och vatten, 2007)
Waterbodies are impaired by, among other things, discharge from onsite small- scale wastewater (WW) treatment systems. Hence, these systems need to be updated to improve the effluent quality and the reuse of nutrients within society. The objectives of this thesis were to find suitable sorbents for a small scale WW treatment system, to investigate the performance of a willow bed in cold climate and to evaluate the function of a proposed WW treatment system adapted to sustainable development in cold climate.Column experiments were performed to study the ammonium adsorption and desorption of clinoptilolite. Laboratory scale studies were conducted to estimate the phosphorus (P) retention of blast furnace slag (BF slag). Further, a full-scale WW treatment system was implemented in northern Sweden to evaluate the function of the system and its units over 16 months. The system comprised of a willow bed and two parallel P filters, namely BF slag and Filtralite-P. A stream of primarily treated WW from a village was pumped to the treatment system.The results from the column experiments showed that ammonium adsorption of the studied clinoptilolite and the desorption of previously adsorbed ammonium was too low to be an economically reasonable alternative for WW ammonium retention in small-scale WW treatment systems.The investigated weathered and coarse-grained BF slag had a low WW P retention, with the overall P sorption below 100 mg P/kg. Therefore, the material is not suitable for P retention. Fresh and fine-grained BF slag demonstrated to be an effective P sorbent in laboratory experiments. However, the release of sulphuric compounds from the BF slag was extensive and may hinder its utilisation as P sorbent.Filtralite-P was found to be a promising P sorbent with a WW P sorption of about 370 mg P/kg at the end of the full-scale experimental period, and still with remaining capacity to retain P.The willow bed functioned as a treatment step due the reduction of nutrients, solids and BOD, and there was no significant ...